Genealogies of fiction : women warriors and the dynastic imagination in the Orlando furioso - Stoppino, Eleonora (Fordham University Press, 2012)
"This book is a study of gender, dynastic politics, and intertextuality in medieval and renaissance chivalric epic, focusing on Ludovico Ariosto's Orlando furioso (1516-1532). Relying on the direct study of manuscripts and incunabula, it challenges the fixed distinction between medieval and early modern texts and reclaims medieval popular epic as a key source for the Furioso. Tracing the formation of the character of the warrior woman, from the Amazon to Bradamante, the book analyzes the process of gender construction in early modern Italy. By reading the tension between the representations of women as fighters, lovers, and mothers, it shows how the warrior woman is a symbolic center for the construction of legitimacy in the complex web of fears and expectations of the Northern Italian Renaissance court."--Publisher's abstract.